1999
DOI: 10.1086/302446
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Dyskeratosis Congenita Is Predominantly Caused by Missense Mutations in the DKC1 Gene

Abstract: Dyskeratosis congenita is a rare inherited bone marrow-failure syndrome characterized by abnormal skin pigmentation, nail dystrophy, and mucosal leukoplakia. More than 80% of patients develop bone-marrow failure, and this is the major cause of premature death. The X-linked form of the disease (MIM 305000) has been shown to be caused by mutations in the DKC1 gene. The gene encodes a 514-amino-acid protein, dyskerin, that is homologous to Saccharomyces cerevisiae Cbf5p and rat Nap57 proteins. By analogy to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 34 publications
(35 reference statements)
2
174
0
1
Order By: Relevance
“…19 Mutation of DKC1 leads to a diseased condition known as X-linked dyskeratosis congentita, which is characterized by abnormal pigmentation, bone marrow failure and an increased susceptibility to cancer. 38,39 Recently, Cayuela et al 40 has shown in transgenic TERT/ TERC À/À mice that the increased expression of TERT, in the absence of TERC genetic background, leads to reduced tumorigenesis, indicating that the tumor-promoting effects of TERT overexpression require the formation of TERT-TERC complexes. In this regard, we propose that rAAVhTERTC27-mediated downregulation of DKC1 may lead to abnormal processing and/or trafficking of hTERTC, which in turn result in telomere destabilization and eventually senescence and apoptosis in the glioblastoma tissues.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%
“…19 Mutation of DKC1 leads to a diseased condition known as X-linked dyskeratosis congentita, which is characterized by abnormal pigmentation, bone marrow failure and an increased susceptibility to cancer. 38,39 Recently, Cayuela et al 40 has shown in transgenic TERT/ TERC À/À mice that the increased expression of TERT, in the absence of TERC genetic background, leads to reduced tumorigenesis, indicating that the tumor-promoting effects of TERT overexpression require the formation of TERT-TERC complexes. In this regard, we propose that rAAVhTERTC27-mediated downregulation of DKC1 may lead to abnormal processing and/or trafficking of hTERTC, which in turn result in telomere destabilization and eventually senescence and apoptosis in the glioblastoma tissues.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%
“…These latter phenotypes, although clinically asymptomatic, often appear first as fatal complications of treatment in the setting of bone marrow transplant and are related to hypersensitivity to preparative chemotherapy and radiation regimens (1,2). The X-linked form of DC presents in the first decade, is most severe, and is a result of mutations in the DKC1 gene (3). The autosomal dominant (AD) form of DC is rare, has a later presentation, and is characterized by mutations in telomerase RNA (hTR) (4).…”
mentioning
confidence: 99%
“…The majority of mutations in DKC1 are missense, and only three non-missense mutations are known: a single amino acid deletion (mentioned above), a deletion of the last exon of the gene and a mutation affecting differential splicing of the mRNA [2,5]. To our knowledge, c.166_167invCT is a novel mutation involving a small inversion in DKC1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the disease-causing mutations are single amino acid substitutions. The substitution A353V has been observed in $30% of X-linked families, frequently as a de novo mutation [2]. Here, we report a Russian pedigree with X-linked DC and a novel mutation of the DKC1 gene.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation